A Retrospective Review of the Management of Lung Cancer Patients Referred into the Regional Neuro-Oncology Pathway in Merseyside, United Kingdom. (1st October 2022) - Heseltine, Jonathan; Corte, Ana; Kennedy, Oliver; Sharples, Harry; Brodbelt, Andrew; Mehta, Shaveta
Abstract: AIMS: Brain metastases (BMs) are common in lung cancer and carry adverse prognostic significance. Such occurrences should be reviewed through a regional specialist neuro-oncology MDT. Our aim is to highlight which aspects of the pathway could be contributing to delays in the treatment of lung cancer patients with BMs. METHOD: All lung cancer patients discussed at the Neuro-Oncology MDT in 2020 were identified. Details of the patient journey through the pathway from diagnosis to death were obtained from the Orion System, regional PACS system, regional neuro-oncology MDT notes and electronic case notes from Clatterbridge. RESULTS: Full datasets were available for 100 patients discussed at the Neuro-Oncology MDT. 49 of these were patients presenting with BMs and lung cancer synchronously. Only 5 out of 13 (38%) of synchronous patients recommended for SRS received this treatment. 7 of 13 patients received a suboptimal treatment (best supportive care or whole-brain radiotherapy). Length of time from neuro-oncology MDT discussion to receiving SRS in the synchronous cohort was 47 versus 20.3 days in the asynchronous group. A review of all 13 cases found that 4 of the 7 cases of CNS-specific deterioration were potentially preventable. Further analysis of these cases revealed common themes of lengthy delays in histological sampling (9), delayed referral or discussion in the appropriate MDT (8) and not jointly referring to neuro-oncology and respiratory oncology (7). CONCLUSION: Lung cancer patients with synchronous BMs receive SRS after full staging and biopsy. There is potential evidence of suboptimal outcomes due to inflexible MDT systems and delays for histology.